2018
DOI: 10.3390/su10072536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poultry-Litter Biochar on Soil Properties and Growth of Water Spinach (Ipomoea aquatica Forsk.)

Abstract: Poultry-litter biochars (PLBs), which were prepared at two pyrolytic temperatures, were applied to the soils of croplands with four consecutive harvests of water spinach to assess the effects of PLBs on the soil properties and the growth of water spinach. The results show that PLB amendment resulted in an increase of soil pH. The electrical conductivity values, and the concentrations of extractable inorganic nitrogen, exchangeable potassium, and available phosphorus in the soils drastically increased in the 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
1
9
0
Order By: Relevance
“…The results obtained for the CCM350 clearly showed that despite about 16.5% loss of the original total N in CM during carbonization at 350 • C, the CCM350 compensated for the N loss through prolonged N retention and increased N bioavailability in soil after application of each amendment at the same rate. In line with our results, Yu et al [60] also reported improved N bioavailability in soil for carbonized CM produced at 350 • C than for the un-carbonized CM. Similarly, Sikder and Joardar [61] found that carbonization of CM in the range of 300 • C produced a material that had superior N bioavailability in soil than the un-carbonized CM.…”
Section: Effect Of Thermal Induced Chemical Alterations Of CM On N Bisupporting
confidence: 93%
See 1 more Smart Citation
“…The results obtained for the CCM350 clearly showed that despite about 16.5% loss of the original total N in CM during carbonization at 350 • C, the CCM350 compensated for the N loss through prolonged N retention and increased N bioavailability in soil after application of each amendment at the same rate. In line with our results, Yu et al [60] also reported improved N bioavailability in soil for carbonized CM produced at 350 • C than for the un-carbonized CM. Similarly, Sikder and Joardar [61] found that carbonization of CM in the range of 300 • C produced a material that had superior N bioavailability in soil than the un-carbonized CM.…”
Section: Effect Of Thermal Induced Chemical Alterations Of CM On N Bisupporting
confidence: 93%
“…Tagoe et al [66] conducted experiments to evaluate the beneficial effects of carbonized and un-carbonized CM on crop productivity, and they reported that the growth and yield of several leguminous crops were enhanced for the CCM than the CM and the control. Similarly, Yu et al [60] reported superior plant growth in CCM fertilized soils in comparison to soils that were fertilized with CM.…”
Section: Effect Of Thermal Induced Chemical Alterations Of CM On N Bimentioning
confidence: 90%
“…47 Application of biochar to the soils of aquatic vegetables including lotus root, water spinach, watercress, and others could effectively improve soil nutrient contents and available state contents. 12,13,18,46 Corn straw biochar addition at 22.5 t ha −1 increased soil total N (TN), available P, and available K contents by 7%, 16%, and 80%, respectively. 46 PB and CB combined with Fe fertilizer also increased the contents of available ammonia N, P and K in watercress soil.…”
Section: Effects Of Biochars On Soil Physicochemical Properties For A...mentioning
confidence: 99%
“…Therefore, to improve the fertility of the soil, remediating polluted water and soil environments and maintaining the ecological balance of the water and soil environment for producing high quality aquatic vegetables have become more and more urgent. It is reported that application of biochars in the cultivation of aquatic vegetables could improve the ooded soil physicochemical properties and fertilities, 12,13 purify the water quality, and alleviate the extent of pollutants, [14][15][16][17][18] which would promote the growth of aquatic vegetables and enhance their yields and qualities.…”
Section: Introductionmentioning
confidence: 99%
“…It is evident from the results of this study that organic amendments improved the leaf surface area of plants grown in treated soil compared to control plants (Figure 2). High nutrient content in PL may have increased plant-available nutrients in the soil, thus improving soil fertility and promoting plant growth (Yu et al, 2018). For instance, nitrogen strongly influences photosynthesis performance and biomass production (Zivcak et al, 2014), the larger the leaf surface area absorbs maximal light (Moseki and Dintwe, 2011) that may contribute to a higher photosynthetic rate, ultimately improving plant growth.…”
Section: Leaf Surface Areamentioning
confidence: 99%